Listening long and late - Everwine, Peter (Pitt poetry series., 2013)
"What a rich array of music lies within Listening Long and Late. With refreshing authenticity, Everwine weds playfulness to practice, lyricism to narrative, pathos to the ordinary. Indeed, he has listened & long and late' to the music of such venerable masters as Tu Fu, the hidden genius on the street, and the anonymous Aztec poets of the fourteenth and fifteenth centuries. Everwine writes with the same 'deified heart' that divines the mystery of his quotidian subjects in a language that is at once plain and poetic. His own work seamlessly segues into his translations from the Hebrew and Nahuatl, as if all the poems belonged to the same poet, which they in fact do, as the glorious multitudes of Peter Everwine, one of the masters of our age"--Chard deNiord